Prevalence and significance of M541L single nucleotide polymorphism in the central European cohort of gastrointestinal stromal tumor patients - Jasek, Karin; Grendar, Marian; Stanclova, Andrea; Malicherova, Bibiana; Kasubova, Ivana; Burjanivova, Tatiana; Szepe, Peter; Ciccocioppo, Rachele; Rodrigo, Luis; Prosecky, Robert; Kruzliak, Peter; Plank, Lukas; et al. (Journal of cancer research and clinical oncology, 2021)
BACKGROUND: Single nucleotide polymorphisms can create a genetic microenvironment in some tumors that affects the course of treatment, resistance, etc. Whether single nucleotide polymorphisms have an impact on gastrointestinal stromal tumor (GIST) development and disease progression is not yet accurately verified. KIT SNPM541L in exon 10 correlates with a worse prognosis of many cancers. The impact of KIT SNPM541L in GISTs is relatively unknown and, therefore, its analyses could have potential in patient therapy and could provide more detailed information on tumor character, clinical presentation, or tumor behavior in treatment. AIM: The aim of the study was the analysis of the biological and clinical significance of the KIT SNPM541L polymorphism in exon 10. MATERIALS AND METHODS: Paraffin sample tissues were obtained from the National GIST Register in Martin. Retrospective samples from 177 GIST patients were divided into several groups. Detection of SNPM541L was performed by Sanger sequencing. Statisitical analyses were performed to determine the prevalence of KIT SNPM541L in the Slovak GIST cohort, to search for correlation between c-KIT status and clinicopathological, molecular and biological data. RESULTS: Overall, 29 samples out of 177 showed KIT SNPM541L polymorphism. CONCLUSION: Our results do not support the association between KIT SNPM541L and increased risk of relapse in localized primary GISTs. Additionally, we found a positive correlation between KIT SNPM541L occurrence and earlier onset of relapse in PDGFRa and WT subgroup of GISTs.
Keywords: senioři; M541L; senioři nad 80 let; jednonukleotidový polymorfismus; Gastrointestinal Neoplasms; Retrospective Studies; Europe; Prognosis; protoonkogenní proteiny c-kit; mladiství; Evropa; Middle Aged; mužské pohlaví; míra přežití; Adult; mladý dospělý; Follow-Up Studies; gastrointestinální nádory; Biomarkers, Tumor; Gastrointestinal Stromal Tumors; následné studie; Proto-Oncogene Proteins c-kit; Aged, 80 and over; Gastrointestinal stromal tumors; Young Adult; ženské pohlaví; nádorové biomarkery; prognóza; Single nucleotide polymorphism; retrospektivní studie; Humans; c-KIT; Survival Rate; gastrointestinální stromální tumory; lidé středního věku; dospělí; Female; Aged; c.1621 A > C; Adolescent; lidé; Male; Polymorphism, Single Nucleotide